New perspectives in signaling mediated by receptors coupled to stimulatory G protein: the emerging significance of cAMP efflux and extracellular cAMP-adenosine pathway. - Godinho, Rosely O.; Duarte, Thiago; Pacini, Enio S. (Frontiers in Pharmacology, 2015)
G protein-coupled receptors (GPCR) linked to stimulatory G (Gs) proteins (GsPCR) mediate increases in intracellular cyclic AMP as consequence of activation of nine adenylyl cyclases (AC), which differ considerably in their cellular distribution and activation mechanisms. Once produced, cyclic AMP may act via distinct intracellular signaling effectors such as protein kinase A (PKA) and the exchange proteins activated by cAMP (Epacs). More recently, attention has been focused on the efflux of cAMP through a specific transport system named multidrug resistance proteins (MRP) that belongs to the ATP-binding cassette (ABC) transporter superfamily. Outside the cell, cAMP is metabolized into adenosine, which is able to activate four distinct subtypes of adenosine receptors, members of the GPCR family: A1, A2A, A2B and A3. Taking into account that this phenomenon occurs in numerous cell types, as consequence of GsPCR activation and increment in intracellular cAMP levels, in this review, we will discuss the impact of cAMP efflux and the extracellular cAMP-adenosine pathway on the regulation of GsPCR-induced cell response.